Synthesis and Absorption Characteristics of Polymer Capped Zinc Oxide Nano Particles Doped in Poly(vinyl alcohol) Film - Ravich, S.; Pushpanathan2, K.; D. Raja3, Franklin; Kalyan3, U. (Asian Journal of Chemistry, 2013)
The ZnO nanoparticles are synthesized by solution method using surfactant. The structure and morphology of the nano particles are investigated by means of X-ray diffraction, high resolution scanning electron microscopy and their absorption properties are also studied. ZnO nanoparticles are dispersed in poly(vinyl alcohol) in different concentrations and a composite film has prepared. The unusual properties are observed in the optical studies. The influence of experimental conditions, such as reaction time, quantity of poly(vinyl alcohol) and concentration of Zn2+, etc. on the quality of the growth mechanism for the formation are discussed. Optical absorption of a film is determined by photoluminescence spectroscopy.